Perancangan Katup Blow Off pada Sistem Turbocharger di Kapal - Khaeroman Khaeroman; Noviarianto Noviarianto; Suyono Suyono (Jurnal Maritim Polimarin, 2018)
This study discusses the design of a Blow Off Valve (BOV) valve in a turbocharger system on a diesel engine on board, BOV is used to release the air pressure contained in the scavenge air chamber when it experiences an increase in pressure due to the reduced frequency of opening the air duct that enters cylinder chamber. The purpose of this study is to analyze the selection of blow off valve designs that are in accordance with the need to reduce surge phenomena on diesel engines of ships using turbocharge and to analyze the quality/ performance results of the blow off valve through Solidwork software. The air pressure will still put pressure to get out of the system. This will cause the pressure in the system to increase and this air pressure will flow back to the turbine and will cause damage to the turbocharge component. This phenomenon is called turbocharge surging. So, air flow is very important to ensure that no air pressure flows back into the turbocharge. The selection of valves in accordance with the design techniques of several alternative choices is very decisive. Numerical calculations and spring performance analysis of a selected valve are carried out using solidwork software.